Avaliação da vulnerabilidade de aquíferos no estado de Sergipe e município de Aracaju - Linhares, Samiramisthaís Souza (2018)
The evaluation of the natural susceptibility of aquifers offers subsidies for the management of water resources and land use and land use planning. The aim of this study was to evaluate the applicability of GOD methods (Foster and Hirata, 1988) and DRASTIC (Aller et al., 1987) in the state of Sergipe and Aracaju, respectively, to determine the natural vulnerability of aquifers. A cadastral survey was carried out with hydrogeological data from the study area, promoting the creation of a database, with technical information, for the registration of the tubular wells, available at Underground Water Information System (SIAGAS) and the Water Resources and Irrigation Development Company of Sergipe (COHIDRO), and later inserted in a Geographic Information System (GIS) for spatialization, interpolation, analysis and interpretation of the data in the two methods. In the State of Sergipe. The study conducted in the State of Sergipe used data from 2,155 tubular wells based on information inherent to the degree of confinement of the aquifer (G), type of production zone lithology (O) and depth of the static level (D), fundamental criteria for applicability of the GOD method. The results obtained ranged from 0 to 0.72, with the vulnerability classified as insignificant to extreme. The lowest values occurred in the Lower São Francisco region, due to the geological context of the area, presenting insignificant vulnerability. The regions of Agreste, Alto Sertão, Centro Sul and Médio Sertão presented vulnerability varying from low to medium. The East and the Great Aracaju are classified as zones of medium and extreme vulnerability, being the highest value registered in the city of Aracaju. Due to the results obtained by the GOD method, the DRASTIC methodology was applied in the Sergipe capital using data from 66 drilled tubular wells in the city of Aracaju. This method takes into account seven parameters: static level depth (D), aquifer recharge (R), lithological composition of the producing area (A), soil type (S), topography of the terrain (T), vadose zone (I) and hydraulic conductivity of the aquifer (C). The results obtained ranged from 112 to 201, according to USEPA (1994), from low to extreme vulnerability. They were classified as areas of reduced fragility (<120) specific regions of the Porto Dantas and Jabotiana communities. The neighborhoods of the west and north of the municipality had, predominantly, medium vulnerability (120 - 160). The southern and central regions of the capital showed high vulnerability (160 - 190) and, in the neighborhoods Surgery and Ponto Novo, reported extreme vulnerability (> 199). It is concluded that the results obtained in this work can corroborate in the decisions that aim at the qualitative protection of groundwater.